Prospects for Australian-Led Regional Cooperation On Asylum Seeker and Refugee Issues - Sian Troath (Andalas Journal of International Studies (AJIS), 2016)
The nomination of former Refugee High Commissioner Antonio Guterres for Secretary-General, the ongoing and intensifying condemnations of Australia’s offshore detention centres on human rights grounds, and the ruling of the Papua New Guinea Supreme Court regarding detention centres on Manus Island, indicate that the Australian government needs a new policy on asylum-seekers. The domestic political demand for a deterrence-based, “no advantage”, tough on borders approach means that the only way to achieve this would be through regional cooperation, which would be impossible without the cooperation of Indonesia. Analysing why there is such strong involvement of domestic politics on this issue, even to the detriment of the bilateral relationship with Indonesia, is vital to understanding how to improve the relationship and foster regional cooperation on asylum seekers. While reaching a broad cooperative agreement on asylum seekers in general would be far too difficult, the Rohingya refugee crisis presents a specific case on which regional cooperation could be built. If successful, this would serve as a building-block for deeper and more sustained regional cooperation on asylum seekers